2014
DOI: 10.1111/nmo.12459
|View full text |Cite
|
Sign up to set email alerts
|

New ghrelin agonist, HM01 alleviates constipation and L‐dopa‐delayed gastric emptying in 6‐hydroxydopamine rat model of Parkinson's disease

Abstract: Background Constipation and L-dopa-induced gastric dysmotility are common gastrointestinal (GI) symptoms in Parkinson’s disease (PD). We investigate the novel ghrelin agonist, HM01 influence on GI motor dysfunctions in 6-hydroxydopamine (6-OHDA) rats. Methods HM01 pharmacological profiles were determined in vitro and in vivo in rats. We assessed changes in fecal output and water content, and gastric emptying (GE) in 6-OHDA rats treated or not with orogastric (og) HM01 and L-dopa/carbidopa (LD/CD, 20/2 mg kg−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 63 publications
(93 reference statements)
1
73
0
Order By: Relevance
“…The goals of the current study were to investigate, in a rodent model of POI, whether systemic administration of novel ghrelin agonists can reverse delayed gastrointestinal transit and determine whether the prokinetic activity of ghrelin occurs through a central and/or peripheral site of action. To address these experimental goals, we used two novel ghrelin agonists: HM01 (N9-[(1S)-1-(2,3-dichloro-4methoxyphenyl)ethyl]-N-methyl-N-[1,3,3-trimethyl-(4R)piperidyl]-urea Hydrochloride), which shows a high binding affinity to the human GHSR-1a (K i 5 1.42 6 0.36 nM) and high brain penetrance, and induces propulsive colonic contractions through a central mechanism involving the stimulation of GHSR-1a receptors on neurons in the lumbosacral spinal cord (Karasawa et al, 2014;Naitou et al, 2015); and HM02 (N9-[(1S)-1-(2,3-dichloro-4-methoxyphenyl)ethyl]-N-hydroxy-N-(1-methyl-4-piperidinyl)-urea), a more peripherally acting ghrelin agonist with low brain penetration (K i 5 3.75 6 0.52 nM; Helsinn, unpublished observations). The effects of the two novel ghrelin agonists were investigated in a rodent model of POI induced by abdominal surgery in which we assessed gastric emptying, the geometric center (GC), and the head of a radiolabeled meal to quantify upper GI transit.…”
Section: Introductionmentioning
confidence: 99%
“…The goals of the current study were to investigate, in a rodent model of POI, whether systemic administration of novel ghrelin agonists can reverse delayed gastrointestinal transit and determine whether the prokinetic activity of ghrelin occurs through a central and/or peripheral site of action. To address these experimental goals, we used two novel ghrelin agonists: HM01 (N9-[(1S)-1-(2,3-dichloro-4methoxyphenyl)ethyl]-N-methyl-N-[1,3,3-trimethyl-(4R)piperidyl]-urea Hydrochloride), which shows a high binding affinity to the human GHSR-1a (K i 5 1.42 6 0.36 nM) and high brain penetrance, and induces propulsive colonic contractions through a central mechanism involving the stimulation of GHSR-1a receptors on neurons in the lumbosacral spinal cord (Karasawa et al, 2014;Naitou et al, 2015); and HM02 (N9-[(1S)-1-(2,3-dichloro-4-methoxyphenyl)ethyl]-N-hydroxy-N-(1-methyl-4-piperidinyl)-urea), a more peripherally acting ghrelin agonist with low brain penetration (K i 5 3.75 6 0.52 nM; Helsinn, unpublished observations). The effects of the two novel ghrelin agonists were investigated in a rodent model of POI induced by abdominal surgery in which we assessed gastric emptying, the geometric center (GC), and the head of a radiolabeled meal to quantify upper GI transit.…”
Section: Introductionmentioning
confidence: 99%
“…Although about a half of the patients suffering from Parkinson's disease experience reduced intestinal motility (29), it is likely because of decreased cholinergic and increased catecholaminergic stimulation (30), and dopaminergic medication (31). The study by Unger et al (32) pointed out the decrease in ghrelin signaling under this catecholaminergic and dopaminergic overstimulation, whereas it should be also noted that Karasawa et al (33) reported confl icting fi ndings in a similar experimental Parkinsonism model. Interestingly, no change in fasting ghrelin in vagotomized patients (34) suggests that disturbed cholinergic transmission is not a determinant for lowered ghrelin levels in Parkinson's disease.…”
Section: Discussionmentioning
confidence: 66%
“…Acute orogastric administration of HM01 in the 6-OHDA rats significantly decreased the 4-hour fecal output and water content, with a dose of 3mg/kg having a maximum effect. Pretreatment with HM01 prevented L-dopa/carbidopa induced delayed gastric emptying, simulating the gastroparesis observed in patients with Parkinson’s disease [28]. It has also been shown that HM01 has a high binding affinity to the human ghrelin receptor, good bioavailability, and it crosses the blood-brain barrier.…”
Section: Early Investigational Therapeuticsmentioning
confidence: 99%